Les lesbiennes - Arc, Stéphanie (Le Cavalier Bleu, 2010)
« Ce sont des garçons manqués », « C’est un choix féministe », « Il y a plus de gais que de lesbiennes », « Elles n’ont pas trouvé le bon », « Entre femmes, ce n’est pas vraiment du sexe », « Elles ne devraient pas avoir d’enfants » … Dépassant, entre autres, le cliché de la « camionneuse », l’auteure nous invite ici à découvrir cette homosexualité féminine qui, depuis Sapho, gêne et inquiète parce qu’elle transgresse les normes sociales.
Section: 1 vol. (127 p.) : couv. ill. ; 18 cm.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Les mères lesbiennes - Descoutures, Virginie; Cairninfo (P.U.F., 2010)
''À partir d'une enquête par entretiens auprès de femmes en couple, cet ouvrage propose une analyse sociologique de la parentalité lesbienne appréhendée à partir de l'exercice du travail parental fourni par les mères. Au-delà des individus, ce sont les deux membres d'un couple qui ont été rencontrés couples de même sexe et ayant élaboré un projet parental, conduisant à diverses configurations familiales organisées autour de l'adoption, la coparentalité, l'insémination artificielle avec donneur connu ou inconnu, ou encore un rapport hétérosexuel.Le but de cette recherche est à la fois de révéler une vie quotidienne peu connue, souvent rendue invisible par le stigmate pesant sur l'homosexualité, et de réfléchir sur « la » famille et le cadre hétéronormatif dans lequel elle se définit. Travailler sur la parentalité lesbienne, c'est en effet interroger par la marge un ensemble de normes régissant le couple et la filiation à l'intersection de la sexualité et de la domination masculine, se demander : comment est-on mère quand on est lesbienne ? Comment est-on mère avec une autre femme, c'est-à-dire quand la « différence des sexes » est absente et quand on n'en a pas le statut légal ? Et, finalement: comment est-on mère « tout court » dans la société contemporaine ?''-
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; couple lesbien; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; maternité; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

“Oh what a world”: Queer Masculinities, the musical construction of a reparative cultural historiography, and the music of Rufus Wainwright - Schwandt, Kevin C. (Université du Minnesota, 2010)
Throughout his ascendancy in fame and cultural visibility, singer/songwriter and gay pop icon Rufus Wainwright's output has been consistently related, by scholars and critics alike, to camp aesthetics, modes of artistic expression typically understood as emerging from queer communities, particularly certain gay male populations, but ones whose political potential is highly contested. Traditional conceptions of camp, as most famously articulated by Susan Sontag in the 1960s, emphasize style over content, necessarily rendering it politically-disengaged. However, scholars have vehemently challenged conceptions like Sontag's, in order to reclaim camp as a potent means to facilitate queer world-making and a powerful resistance to heteronormativity. I examine Wainwright's image and music in order to theorize a new queer interpretive listening position. Specifically, I draw upon the literary perspective of “reparative reading,” articulated by Eve Kosofsky Sedgwick in opposition to what she describes as “paranoid reading,” to propose a uniquely queer approach to musical and cultural historiography, exemplified by Wainwright's music. Much of the current queer musicology focuses on lost histories, systematic marginalization, and the commoditization of queer identities. While such approaches have produced important insights, thorough examination of the relationships between queer cultural products and their queer reception has proven elusive. This project suggests a unique approach to understanding the musical construction of a specific kind of queer masculinity, one which combines authorial creation with reparative conceptions of reception, in order to theorize a uniquely gay male interpretive position. When viewed through a theoretical lens combining politically-potent conceptions of camp performativity with a reparative reading position, Wainwright's music strikingly enacts Philip Brett's call to claim, not historical evidence, but the right of interpretation, emerging as an act of resistance via the reclamation and consolidation of a queer interpretive authority. In this way, Wainwright articulates both a rupture in the history of queer masculinity and a powerful means of resistance to the often-exclusionary relationships between literary, musical, and artistic objects and the heteronormative cultural systems in which they are created.
https://hdl.handle.net/11299/100915
Keywords: 2000 à aujourd'hui; 2000-2009; DIG; LGBTQIA2+; approches et analyses; arts; culture populaire; discipline; historiographie; hétérosexisme; identités LGBTQIA2+; masculinité; musique; mémoires/thèses; périodes historiques; queer; ressource en ligne; résistance; systèmes d'oppressions; thématiques